Ecthyma gangrenosum without bacteraemia: evidence in favour of a broader definition. (27th February 2017) - Ferguson, L.; Chong, H.; Singh, M.
Summary: Ecthyma gangrenosum (EG) is often defined as a cutaneous manifestation of Pseudomonas aeruginosa septicaemia, typically secondary to neutropenia. There is increasing recognition that a broader definition is warranted, as numerous causative organisms and predisposing conditions have been reported. We describe two cases of EG that occurred without bacteraemia. In this atypical subset of cases, the skin is thought to represent the primary inoculation site from which haematogenous spread can occur. The first case occurred in the context of human immunodeficiency virus (HIV) infection, a rarely reported association. The evidence base guiding clinicians on management of EG is very limited, particularly in relation to patients with HIV, in whom recurrence risk may be higher than normal. Recurrent EG is described in our second case, in an individual with Good syndrome, a rare association of thymoma and immunodeficiency.